Quercetin for the treatment of COVID‐19 patients: A systematic review and meta‐analysis. (13th February 2023) - Cheema, Huzaifa Ahmad; Sohail, Aruba; Fatima, Areej; Shahid, Abia; Shahzil, Muhammad; Ur Rehman, Mohammad Ebad; Awan, Rehmat Ullah; Chinnam, Sampath; Nashwan, Abdulqadir J.
Abstract: Currently approved therapies for COVID‐19 are mostly limited by their low availability, high costs or the requirement of parenteral administration by trained medical personnel in an in‐hospital setting. Quercetin is a cheap and easily accessible therapeutic option for COVID‐19 patients. However, it has not been evaluated in a systematic review until now. We aimed to conduct a meta‐analysis to assess the effect of quercetin on clinical outcomes in COVID‐19 patients. Various databases including PubMed, the Cochrane Library and Embase were searched from inception until 5 October 2022 and results from six randomized controlled trials (RCTs) were pooled using a random‐effects model. All analyses were conducted using RevMan 5.4 with odds ratio (OR) as the effect measure. Quercetin decreased the risk of intensive care unit admission (OR = 0.31; 95% confidence interval (CI) 0.10–0.99) and the incidence of hospitalisation (OR = 0.25; 95% CI 0.10–0.62) but did not decrease the risk of all‐cause mortality and the rate of no recovery. Quercetin may be of benefit in COVID‐19 patients, especially if administered in its phytosome formulation which greatly enhances its bioavailability but large‐scale RCTs are needed to confirm these findings.